2007
DOI: 10.1007/s11095-007-9479-x
|View full text |Cite
|
Sign up to set email alerts
|

Increasing the Dissolution Rate of Itraconazole Processed by Gas Antisolvent Techniques using Polyethylene Glycol as a Carrier

Abstract: Using ASES, microparticles of itraconazole were produced with an increased dissolution rate compared with raw material and commercially available product.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 34 publications
1
21
0
Order By: Relevance
“…5 The use of supercritical fluids for the production of microparticles/ nanoparticles is of great interest in recent years due to advantages such as low or no residual solvent in the process, a narrow particle size distribution, effective deagglomeration of the cohesive drug particles, and increased dissolution rate profiles. 2,14,[25][26][27][28]32 Among different methods using supercritical fluids, precipitation using supercritical carbon dioxide (CO 2 ) as an antisolvent is well known and has been used to micronize several kinds of compounds. CO 2 is an ideal supercritical fluid because of its low critical temperature (31.18…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 The use of supercritical fluids for the production of microparticles/ nanoparticles is of great interest in recent years due to advantages such as low or no residual solvent in the process, a narrow particle size distribution, effective deagglomeration of the cohesive drug particles, and increased dissolution rate profiles. 2,14,[25][26][27][28]32 Among different methods using supercritical fluids, precipitation using supercritical carbon dioxide (CO 2 ) as an antisolvent is well known and has been used to micronize several kinds of compounds. CO 2 is an ideal supercritical fluid because of its low critical temperature (31.18…”
Section: Introductionmentioning
confidence: 99%
“…46 Itraconazole (ITZ) is a highly water-insoluble drug (solubility ∼1 ng/mL) and categorized as a BCS class II compound. 32 Different methods such as complexation with cyclodextrins, 47 solid dispersions, 48 eutectic mixtures, 49 and nanoporous silica 50 were utilized to improve the solubility and dissolution of this drug. Recently, it has been demonstrated that ITZ in its supersaturated state provokes formation of nanofibers leading to reduction of transepithelial transport across Caco-2 cell monolayers.…”
Section: Introductionmentioning
confidence: 99%
“…Under the SEM, untreated ITZ was observed as columnar crystals made up of irregular shaped rectangular prisms with a wide size distribution ( Fig. 1a) (Barrett et al, 2008). Evaporative recrystallization was used for transition of crystalline to amorphous phase.…”
Section: Crystal Morphologymentioning
confidence: 99%
“…Vaginal candidiasis, a commonly reported affliction in women throughout the world, was selected as a target disease while itraconazole, a potent synthetic triazole antifungal drug with activities against broad spectrum of fungal species (Saag & Dismukes, 1988) was chosen as target drug moiety. Itraconazole has gained popularity in the literature as ''practically impossible to apply to the body'' (Barrett et al, 2008). Solid lipid nanoparticles (SLNs) have gained popularity for being a suitable carrier for hydrophobic drugs and have been successfully used for dermal and mucosal delivery.…”
Section: Introductionmentioning
confidence: 99%